Patient Experience in a Spanish Pediatric Emergency Department. Issue 8 (August 2020) - Parra, Cristina; Carreras, Nuria; Vergés, Alba; Trenchs, Victoria; Luaces, Carles
Abstract : Objectives: To study the experience reported by pediatric patients when visiting a pediatric emergency department (PED). Methods: This was a prospective descriptive study, carried out in November 2014. A 12-question survey was developed, based on the Picker Patient Experience Questionnaire. The aim was to assess patient experience of children between 8 and 18 years old, attended in the PED of a high-complexity pediatric hospital. Questions were about the waiting time and setting, medical staff explanations and actions, treatment, and discharge. The questionnaires were administered and filled in by the children themselves at discharge. Results: One-hundred seventy questionnaires were completed; 17.1% of respondents had to wait longer than expected, and 44.7% said that there was not enough to do when waiting to be seen. Pain was not correctly treated (3%), there was a lack of privacy (14.7%), and the information provided to the patients during the visit was wanting (10%). However, 80% said that they had been well treated. Conclusions: The patient experience of children in our PED was positive, although some aspects should be improved such as offering entertainment in the waiting area, increasing privacy during the medical visit, and giving better explanations to the children.